Refractory cytomegalovirus infections in Chinese patients receiving allogeneic hematopoietic cell transplantation: a review of the literature - Yang, Donglin; Yao, Yuanyuan; Sun, Yi; Jiang, Erlie (Frontiers in Immunology, 2023)
In the absence of prophylactic therapy, cytomegalovirus (CMV) viremia is a common complication following allogeneic hematopoietic cell transplantation (allo-HCT) and represents a significant cause of morbidity and mortality. Approximately 25% of allo-HCT happen in China, where the development and refinement of the 'Beijing protocol' has enabled frequent and increasing use of haploidentical donors. However, refractory CMV infection (an increase by >1 log10 in blood or serum CMV DNA levels after at least 2 weeks of an appropriately dosed anti-CMV medication) is more common among patients with haploidentical donors than with other donor types and has no established standard of care. Here, we review the literature regarding refractory CMV infection following allo-HCT in China.Donglin Yang designed the study, conducted literature search, performed data analysis and wrote the manuscript. Yuanyuan Yao contributed to study design, conducted literature search, performed data analysis and wrote the manuscript. Yi Sun contributed to study design, conducted literature search, performed data analysis and wrote the manuscript. Erlie Jiang designed the study, supervised the research and provided critical revision.This review was funded and sponsored by MSD China.